Zakat Sebagai Pengentasan Kemiskinan dan Pembangunan Perekonomian Umat (Telaah Pengelolaan Zakat Pada Masa Khulafaur Rasyidin) - Mutia Azizah Nuriana; Khomarudin Achmad (TERAJU: Jurnal Syariah dan Hukum, 2020)
This article discusses the function of zakat in people's lives during the khulafaurasyidin period descriptively. By using a social history approach, the socio-economic life during the Khulafaur Rasyidin period, particularly in relation to the application of zakat. During the reign of Khulafaurasyidin zakat became the main instrument in alleviating poverty and building the economy of the people. The policies issued by the caliphs all led to poverty alleviation and also the economic development of the people. In alleviating poverty through service and assistance facilities. Meanwhile, in the economic development of the people through zakat empowerment, Zakat has a role and function simultaneously, spiritually and socially, so that zakat can be a solution to problems of poverty and economic development.